Timely access to inpatient rehabilitation after stroke: a qualitative study of perceived barriers and potential solutions in Ontario, Canada. Issue 26 (18th December 2018) - Meyer, Matthew J.; Teasell, Robert; Kelloway, Linda; Meyer, Samantha B.; Willems, Deborah; O'Callaghan, Christina
Abstract: Purpose: Stroke units have been established as best practice care, in part because they offer timely initiation of rehabilitation. Experts in Ontario, Canada recommend that eligible patients be transferred to inpatient rehabilitation (on average) by day 5 after ischemic stroke and day 7 after a hemorrhagic stroke. This study explores perceived barriers to implementation of these recommendations and potential solutions. Method: Exploratory focus groups were held with stakeholders from five geographically diverse regions across Ontario between September 2011 and January 2012. Participants were asked to consider the recommendations, list perceived barriers and to collectively discuss potential solutions. Data analysis included coding of transcribed data, sorting material to identify themes and confronting themes with a formalized body of knowledge. Results: Barriers identified by participants fell into three categories: patient-centered, clinician-focused and resource or system based, within these, specific challenges included managing patients' medical and emotional readiness for rehabilitation, timely completion of medical tests, staff comfort in discharging patients, dedicated transportation and funding-related concerns. Conclusions: The structure of Ontario's health care system presents challenges to early transfer of stroke patients to inpatient rehabilitation, yet the stakeholders consulted in this study felt that these could be addressed with proper planning, improved coordination and targeted investment. Implications for rehabilitation: Stroke units are a well-established best practice in stroke care and timely access to rehabilitation is a key component of their effectiveness. Stroke experts in Ontario, Canada recommend transfer of suitable patients to inpatient rehabilitation on day 5 and day 7, on average, after ischemic and hemorrhagic stroke, respectively. Stakeholders report that meeting these targets may require some adjustments to local processes of care, many of which can be achieved with little to no financial investment.